Comprehensive and Systematic Study on the Fault Tolerance Architectures in Cloud Computing - Mohammadian, Vahid; Navimipour, Nima Jafari; Hosseinzadeh, Mehdi; Darwesh, Aso (Journal of circuits, systems, and computers, 2020)
Providing dynamic resources is based on the virtualization features of the cloud environment. Cloud computing as an emerging technology uses a high availability of services at any time, in any place and independent of the hardware. However, fault tolerance is one of the main problems and challenges in cloud computing. This subject has an important effect on cloud computing, but, as far as we know, there is not a comprehensive and systematic study in this field. Accordingly, in this paper, the existing methods and mechanisms are discussed in different groups, such as proactive and reactive, types of fault detection, etc. Various fault tolerance techniques are provided and discussed. The advantages and disadvantages of these techniques are shown on the basis of the technology that they have used. Generally, the contributions of this research provide a summary of the available challenges associated with fault tolerance, a description of several important fault tolerance methods in the cloud computing and the key regions for the betterment of fault tolerance techniques in the future works. The advantages and disadvantages of the selected articles in each category are also highlighted and their significant challenges are discussed to provide the research lines for further studies.